The horse and his boy - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : Macmillan, 1954)
Bree, a talking horse, and Shasta, a young boy, are joined by the four English children and Aslan to help save Narnia from invasion.
Sequel to: The Silver chair.
970
Keywords: Fantasy; Fantasy fiction